The 7 habits of highly effective people : powerful lessons in personal change - Covey, Stephen R., 4 0 16; (James Charles), 1958- Collins, James C.;Covey, Sean; 5 (New York : Simon & Schuster, 2017)
One of the most inspiring and impactful books ever written, The 7 Habits of Highly Effective People has captivated readers for nearly three decades. It has transformed the lives of presidents and CEOs, educators and parents--millions of people of all ages and occupations. Now, this 30th anniversary edition of the timeless classic commemorates the wisdom of the 7 habits with modern additions from Sean Covey. The 7 habits have become famous and are integrated into everyday thinking by millions and millions of people. Why? Because they work!With Sean Covey's added takeaways on how the habits can be used in our modern age, the wisdom of the 7 habits will be refreshed for a new generation of leaders
Foreword -- Preface to the 30th anniversary edition by Sean Covey -- Part one: Paradigms and principles -- Inside-out -- The 7 habits-an overview -- Part two: Private victory -- Habit 1: be proactive -- Habit 2: begin with the end in mind -- Habit 3: put first things first -- Part three: Public victory -- Habit 4: think win/win -- Habit 5: seek first to understand, then to be understood -- Habit 6: synergize -- Part four: Renewal -- Habit 7: sharpen the saw -- Inside-out again -- New insights on inside-out again -- Afterword: Q & A with Stephen R. Covey -- A quadrant II day at the office -- A Covey Family tribute to a highly effective father
Updated with fresh insights by Sean Covey--Cover
Includes bibliographical references and indexes
Also issued online
Keywords: 2 -- 0; 6; Psychological aspects. -- Success;Character. -- 20; 20; 2